Acute effects of sodium citrate supplementation on competitive performance and lactate level of elite fitness challenge athletes: A crossover, placebo-controlled, double-blind study - Magshoud Nabilpour; Amira Zouita; Jerry Mayhew; Gholam Rasul Mohammad Rahimi; Yaser Alikhajeh; Morteza Taheri; Khadijeh Irandoust; Leila Youzbashi; Urs Granacher; Hassane Zouhal (Elsevier, 2024)
Background/Objective: The performance of sodium citrate has been investigated in high-intensity exercises, but fewer studies have addressed the role of citrate in weight-bearing exercises. Methods: Twenty fitness challenge athletes, aged 24-32 years, volunteered to participate in this crossover, placebo-controlled, double-blind study. Initially, ten athletes were given a placebo and asked to complete a fitness challenge (i.e., chin-ups, squat jumps, dips, walking lunges, sit-ups, and burpees-devil press). Another ten athletes were supplemented with sodium citrate 0.5 g/kg body mass supplements 3 h prior to performing the fitness challenges. The same procedures were completed two days later with the supplement and placebo dextrose groups switched in a cross-over design. Athletes and assessors were blinded for the experimental condition (placebo vs. verum). Lactate levels were measured 5 min after exercise. The athletes' performance on each item of the fitness challenge as well as their lactate levels, were compared. Differences between the means of the measured variables were contrasted using a dependent t-test. Results: Supplementing sodium citrate substantially improved athletes' performance in all six fitness challenge items (p < 0.05, 0.69<Cohen's d < 2.52, moderate to large). In addition, lactate levels registered after the fitness challenge were lower in the citrate sodium supplementation vs. placebo condition (p = 0.001, Cohen's d = 0.63, moderate). Conclusion: Acute sodium citrate supplementation may help fitness challengers postpone muscular fatigue and increase performance, potentially via the prevention of lactate accumulation.